Answer :

For P(x,y)


X = (– 10 – 2)/2 = – 6


Y = (4 + 0)/2 = 2


Thus, P(– 6,2)


Now


– 6 = (m1x2 + m2x1)/ m1 + m2


– 6 = (m1(– 4) + m2(– 9))/ m1 + m2


– 6 = (– 4m1 – 9m2)/ m1 + m2


– 6(m1 + m2) = – 4 m1 – 9 m2


– 2m1 = – 3m2


m1:m2 = 3:2,


2 = (m1y2 + m2y1)/ m1 + m2


2 = (3 × y + 2x (– 4))/5


2 = (3y – 8)/5


10 = 3y – 8


3y = 18


y = 6


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses